The impact of the built environment on creativity in public spaces of Dutch university campuses and science parks. Issue 1 (2nd January 2022) - Soares, Isabelle; Venhorst, Viktor; Weitkamp, Gerd; Yamu, Claudia
ABSTRACT: Studies on university campuses public spaces have recognized that there is a significant relationship between the built environment and people's perceptions of creativity. There is, however, little empirical evidence to support this claim. This research quantifies and measures this relationship, defined as 'spatial affordances for creativity', using two types of Dutch university campuses as case studies: inner-city campuses and science parks (SPs). This study found statistical associations that locations of built environment features influenced creativity between people. Moreover, spatial affordances for creativity must be considered in the planning and design of campuses, as a suite of spatial and perceptual conditions.